Still in Uniform: Treating Active Military Members in a Civilian Psychiatric Facility. (1st October 2016) - Levitt, Gwen A.; Weller, Jennifer; Koster, Felicitas; Palmer, James
ABSTRACT: Admissions of military members (MMs) to community psychiatric hospitals are increasingly common, bringing unfamiliar challenges to civilian providers. To broaden the knowledge base on psychiatric issues facing MMs, investigators collected demographic and clinical variables from medical records of inpatients treated on a community hospital unit that specializes in MM treatment. Military members in this study had high rates of post-traumatic stress disorder (PTSD), depression, anxiety, and substance use disorders. Future research and information focusing on the psychiatric needs of MMs is greatly needed. Educating community mental health providers to help them better understand the unique challenges of working with active duty MMs will improve care and outcomes.